The FamilyMart Experience: Key Drivers of Customer Satisfaction in Malaysia’s Convenience Retail Sector - Ng Wei Chien; Yap Hui Ling; Xu Ke; Xu Menghan; Xu Sitong; Divya Chandrakant Pai; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
FamilyMart, a Japanese convenience store franchise in Malaysia since 2016, has quickly become a leading retailer offering Japanese-style food, beverages, and lifestyle products. This study aims to examine the key factors influencing customer satisfaction at FamilyMart Malaysia, focusing on customer experience. Data were collected from 152 customers via online surveys and analyzed with SPSS to test the hypotheses. The findings indicate that store atmosphere, convenience, and service quality have a significant positive impact on the FamilyMart customer experience in Malaysia. Additionally, both service quality and customer experience significantly enhance customer satisfaction. The results further demonstrate a positive relationship between customer experience and satisfaction, suggesting that improvements in the overall shopping experience directly contribute to higher satisfaction levels. These outcomes underscore the critical roles of store atmosphere, convenience, service quality, product quality, and customer experience in shaping customer perceptions and satisfaction within Malaysia’s convenience retail sector. The study concludes that enhancing customer experience boosts satisfaction, highlighting the need for FamilyMart to focus on staff training, consistent product quality, and strategic resource allocation to remain competitive in Malaysia’s retail market.